Shaping the Past in the Historic Centers of Šibenik and Split after 1945 - Špikić, Marko (Array, 2016)
The paper discusses the rebuilding of the historic centers of Šibenik and Split in the aftermath of the Second World War. The authors examine the earlier appropriation of Dalmatian cultural heritage by Italian authors in relation to the postwar perspectives given by Croatian art historians, architects and conservators. In tracing this relation, they consider how the war destruction and great demographic changes brought about a revision of the two previously dominant conservation traditions, the Central-European and Italian ones. The examples of Šibenik and Split are taken to explain the issues of the politically charged perception and treatment of bombed urban areas. After the war, the centers of these cities witnessed a redefinition of the collective memory, realized through different interventions to their built fabric: from the implementation of the conservation methods promoted by Gustavo Giovannoni (isolamento, diradamento edilizio and reintegrazione con la demolizione) to facsimile reconstructions of demolished buildings. The authors furthermore seek to explore the relationship between preservation and architectural creation, both in the context of new buildings inserted in the existing setting (the case of Ivan Vitić’s architecture) and architects’ approach to historic cities and urban areas (the architectural theories of Nikola Dobrović). All these topics are viewed against the backdrop of the political and social changes taking place during the early years of socialist Croatia.